Pathogenicity of entomopathogenic fungi to eggs, larvae, and adults and their effects on development of Aedes albopictus - INDRI RAMAYANTI; SITI HERLINDA; AHMAD MUSLIM; HAMZAH HASYIM; CHAIRIL ANWAR; SUWANDI SUWANDI; NURHAYATI DAMIRI; CHANDRA IRSAN; MARIESKA VERAWATY (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Ramayanti I, Herlinda S, Muslim A, Hasyim H, Anwar C, Suwandi S, Damiri N, Irsan C, Verawaty M. 2023. Pathogenicity of entomopathogenic fungi to eggs, larvae, and adults and their effects on development of Aedes albopictus. Biodiversitas 24: 4766-4774. No information is available on the effect of fungi on the development of Aedes albopictus and the effectiveness of fungi in killing its eggs, larvae, and adults. The aim of this research was to determine the pathogenicity of entomopathogenic fungi on the eggs, larvae, and adults of Ae. albopictus and to investigate the effects of the fungi on the development of Ae. albopictus. The fungal species identified molecularly were Aedes albopictus, Beauveria bassiana, Metarhizium anisopliae, Penicillium citrinum, and Talaromyces diversus. The results showed that entomopathogenic fungi negatively affected the development of Ae. albopictus and could decrease the eggs laid by adult females and shorten adult longevity. M. anisopliae was the most pathogenic fungal species (mortality rate 100%) for eggs, larvae, pupae, and adults of Ae. albopictus. However, B. bassiana, P. citrinum, and T. diversus were also found pathogenic to them. The effect of eggs treated with entomopathogenic fungi negatively affected the larval, pupal, and adult stages of Ae. albopictus. These findings highlighted that M. anisopliae, B. bassiana, P. citrinum, and T. diversus have insecticidal activity against Ae. albopictus eggs, larvae, pupae, and adults. Therefore, further investigation is needed to develop these fungal species into ovicides, larvicides, and adulticides to control Ae. albopictus.